2017
DOI: 10.1248/bpb.b17-00141
|View full text |Cite
|
Sign up to set email alerts
|

Anti-stress Effect of Green Tea with Lowered Caffeine on Humans: A Pilot Study

Abstract: Theanine, an amino acid in tea, has significant anti-stress effects on animals and humans. However, the effect of theanine was blocked by caffeine and gallate-type catechins, which are the main components in tea. We examined the anti-stress effect of green tea with lowered caffeine, low-caffeine green tea, on humans. The study design was a single-blind group comparison and participants (n=20) were randomly assigned to low-caffeine or placebo tea groups. These teas (≥500 mL/d), which were eluted with room tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 35 publications
(53 reference statements)
0
14
0
Order By: Relevance
“…Overall, several studies have shown that the administration of L-theanine improved anxiety and stress outcomes, alongside improvements in other manifestations such as depression and psychopathological symptoms ( Table 1). An overall improvement in anxiety symptoms was often accompanied by improvements in biomarkers, including salivary α-amylase, cortisol, chromogranin A and immunoglobulin A [27][28][29][30]. White and colleagues, employing the technique of magnetoencephalography, found that posterior resting alpha activity was significantly higher in the high trait anxiety group receiving L-theanine as compared to the matched placebo group [29].…”
Section: Anxiety and Stress Outcomesmentioning
confidence: 99%
“…Overall, several studies have shown that the administration of L-theanine improved anxiety and stress outcomes, alongside improvements in other manifestations such as depression and psychopathological symptoms ( Table 1). An overall improvement in anxiety symptoms was often accompanied by improvements in biomarkers, including salivary α-amylase, cortisol, chromogranin A and immunoglobulin A [27][28][29][30]. White and colleagues, employing the technique of magnetoencephalography, found that posterior resting alpha activity was significantly higher in the high trait anxiety group receiving L-theanine as compared to the matched placebo group [29].…”
Section: Anxiety and Stress Outcomesmentioning
confidence: 99%
“…To enhance the stress-reducing effect of green tea, low-caffeine green tea with reduced caffeine content can be prepared from tea leaves by irrigating them with hot water at 95 °C for three minutes. Published data showed that a significant stress-reducing effect of low-caffeine green tea was observed in participants in their 20 s, 40 s–50 s, and 80 s–90 s relative to barley tea or standard green tea [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since green tea is generally eluted with hot water, the eluate is rich in EGCG and caffeine. However, the solubility of EGCG and caffeine is low in room temperature water (EGCG is <5 mg/mL and caffeine is 22 mg/mL) [ 12 ]. On the other hand, the solubility of theanine is high (370 mg/mL), even at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in this experiment, we examined the anti-stress effect of SGT and LCGT that had been eluted with room temperature water. Indeed, the ingestion of LCGT that was steeped in room temperature water significantly suppressed the stress response in mice and in young individuals [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%